Ultrasonic pre-treatment on the replacement of high concentration of cadmium(Ⅱ) by aluminum powder: Effect and mechanism - Tian Wang; Yuanru Wang; Hongtu Ji; Yimin Zhang; Deyang Song; Phan Duc Lenh; Thiquynhxuan Le; Libo Zhang (Ultrasonics Sonochemistry)
Cadmium (Cd) is a toxic metal with significant recycling value. Our previous work demonstrated that ultrasonic-enhanced Cd2+ replacement by aluminum (Al) powder outperforms non-sonicated methods, yet challenges remain in treating high-concentration Cd2+ solutions. This study introduces an ultrasonic pre-treatment for Al powder to enhance Cd2+ replacement in high-concentration solutions. The effects of pre-treatment time, temperature, pH, and ultrasonic power density on the replacement efficiency were systematically investigated. Under optimized conditions, the Cd2+ replacement degree increased by 20.7 % compared to non-pre-treated Al and 3.87 % compared to conventionally pre-treated Al, reaching 97.53 %. Ultrasound corrodes the Al powder’s oxide film, reducing its inhibition on electron release and creating a favorable atmosphere for enhanced replacement. The specific surface area of ultrasonically pre-treated Al powder increased by 35 % and 92 % compared to conventionally pre-treated and non-pre-treated Al, respectively, enhancing Cd2+ reaction. This process enables efficient treatment of higher Cd2+ concentrations (300 % increase) with lower Al powder consumption (40 % decrease), making it more suitable for industrial-scale, efficient, clean, and sustainable production.